Antibacterial evaluation of 2, 4-dihidroxy benzoic acid on Escherichia coli and Vibrio alginolyticus. (July 2020) - Ngurah, Budiana I Gusti M.; Ni Nyoman, Yuliani; Dafroyati, Yuliana; Gede Aris Gunadi, I; Taneo, Malkisedek
Abstract: In recent years, human pathogenic microorganisms have developed resistance in response to the indiscriminate use of commercial antimicrobial drugs commonly employed in the treatment of infectious diseases. Therefore, research to discover the new anti-bacterial compounds is important to do. This study was carried out with an objective to synthesis and invaluated the antibacterial potentials of 2, 4-dihidroxy benzoic acid. The aim of the study is to synthesis and assess the antimicrobial activity and to determine the zone of inhibition of on Escherichia coli and Vibrio alginolyticus . The synthesis of 2, 4-dihidroxy benzoic acid was conducted by reacting 2, 4-dihidroxy benzene and carbon dioxide. The characterization of the target compounds was performed by IR and MS spectrometers. The growth of the tested bacteria was observed using a colony counter to see the diameter of the resistance which was caused by the test solution. The antibacterial activity test indicated that 2, 4-dihidroxy benzoic acid had the potential as an antibacterial against Escherichia coli and Vibrio alginolyticus . The synthesis product was obtained as a white solid, melting point 168-169 °C, 67.5 % yield and 97.5 % purity. The activity was known from its inhibition zone. At the concentration of 100 ppm, 2, 4-dihidroxy benzoic acid solution showed the diameter of the inhibitory zone was 17.8 mm and 17.0 mm respectively, while amoxicillin antibiotic showed of 16.6 mm. These results indicate that 2, 4-dihidroxy benzoic acid have a greater strength than amoxicillin in inhibiting bacterial growth Escherichia coli and Vibrio alginolyticus .